CRITICAL ANALYSIS OF THE CONCEPT OF HUMAN CAPITAL: BEYOND MATHEMATICAL MODELS (Third Sector Social Economic Review, 2025)
The 20th century witnessed many steps taken to ensure the exploitation and control of labour, the main subject and sole creative element of the capitalist production process, by capital. It can be said that the period in which capitalist workplace management, whose historical background can be traced back to the 18th century, came into existence in its ‘modern’ form and with all its elements, largely coincides with the 20th century.The capitalist management of the process of production and labour has made use of the possibilities offered by techno-science, as well as the theoretical and practical advice of the social sciences, to the extent that it has deemed it useful. In this framework, the study emphasises that human capital theory occupies a place that should not be underestimated in the ‘useful scientific material’ stock of the capitalist class with its ‘theoretical’ dimension that mystifies the exploitation of educated workers, as well as its practical dimension that can guide education and labour power policies, and aims to critically examine the basic dynamics of capitalist production management and its effects on labour.
Keywords: Human capital theory; education and productivity; surplus value; labour and labour power analysis; the capitalist system of production